Analysis Of The Level Of Passing Skillsinner Leg Passing Skills In Players U 19 Futsal Players At Tanjung Bungau Fc - Setiawan, Derri; Perdima , Feby Elra; Banat, Azizatul (Journal of Education, 2025)
This study aims to determine the level of passing skills of the inner leg of U 19 futsal players at Tanjng Bungau FC. This research is a type of descriptive research. the population in this study were all 20 people. This sampling was done using total sampling technique which amounted to 20 people. This research instrument is through observation in a futsal match. Data analysis techniques using frequency distribution analysis techniques with percentage calculations P = F / N x100%.The results of the study, namely, the assessment of three judgment people with a Likert scale of 20 samples on the inner foot passing skill (57.17%), classified as a sufficient category